PENGEMBANGAN GAME INTERAKTIF MENGGUNAKAN PLATFORM WORDWALL.NET SEBAGAI ALAT EVALUASI HASIL BELAJAR MATERI PECAHAN KELAS IV - Filahanasari, Eka; Wahyuni, Rahmi Juwita; Efendi, Raimon (Universitas Bhinneka PGRI, 2023)
This study aims to develop interactive games as an evaluation tool to be a solution to this problem. This study uses the ADDIE development model with its stages namely analysis, design, development, implementation and evaluation. From the results of the study it was found that the game developed was very valid with a final percentage of 84.3% which was assessed by 3 expert validators namely media, material and language experts. Assessment of product practicality using a student response questionnaire with a percentage result of 97.5% and a teacher response questionnaire with a percentage result of 97,9% is categorized as very practical. Furthermore, the effectiveness obtained from the student perception questionnaire on the game obtained the final percentage of 95.5% categorized as very effective and the level of agreement with the category strongly agreed on each aspect of the assessment.